Impact of COVID-19 on municipal government employees and Well-being in Limpopo Province, South Africa - Malebajoa Anicia Maoela; Godwell Nhamo (Discover Public Health)
Abstract The global impact of COVID-19 affected organisations and workers in all sectors, fundamentally altering daily life and work routines. However, there has been relatively little examination of how these implications vary across different management levels and job categories. This study investigated the impact of the COVID-19 on municipal employees in the Limpopo Province of South Africa. Research focused on four key areas: productivity, mental health, private life, and self-reported health. A cross-sectional survey was used, with data collected from 194 employees through an e-survey platform that was administered physically. The questions were primarily closed-ended, with some structured open-ended questions to capture additional insights. Statistical analyses, including ANOVA and linear regression were performed to assess the associations. The findings demonstrate the varied effects of COVID-19 among job categories. The impact of COVID-19 extended beyond health concerns, positively correlating with family deaths, variation in mental health, and disruptions in work productivity as well as personal lives. Despite widespread coverage of vaccinations and remote work opportunities during lockdowns, the COVID-19 took a toll on both personal and professional fronts, with significant proportions of respondents experiencing personal losses, economic stress, and challenges to mental health. The variability in awareness of COVID-19-related fatalities between departments underscored the importance of transparent communication and rapid responses within organisations. These findings provide crucial insights into the complex interplay of COVID-19's effects on individuals' health, work dynamics, and personal lives, emphasising the need for holistic strategies to mitigate its far-reaching consequences.